Neonatal factors associated with preterm infants' readmissions to the neonatal intensive care units - Elahe Dashti; Maryam Rassouli; Leila Khanali Mojen; Asma Puorhoseingholi; Azam Shirinabady Farahani; Fatemeh Sarvi (Tehran University of Medical Sciences, 2015)
Background & Aim: Preterm infants are at increased risk for readmission after discharge from the neonatal intensive care unit. Some factors and characteristics of preterm infants have an effect on their readmissions. This study aimed to determine neonatal factors related to preterm infants' readmissions to the neonatal intensive care unit. Methods & Materials: This correlational study was conducted on a sample of preterm infants admitted to the neonatal intensive care unit at three teaching hospitals of Shahid Beheshti University of Medical Sciences in 2013. Samples were studied using a questionnaire on possible factors and characteristics related to readmission including sex, gestational age, birth weight, multiple birth and length of stay in the neonatal intensive care unit after discharge. The infants were also followed for readmission thirty days after discharge. The data were initially analyzed by univariate analysis and then by the logistic regression model. Results: The results of univariate analysis revealed that the infants readmitted at the time of follow up were significantly more premature and had lower birth weight and a longer initial hospital stay in the neonatal intensive care units (P<0.001). In the logistic regression model, only gestational age and birth weight had a significant statistical association with infants' readmission (R: 0.805, P=0.001 and odds ratio: 0.998, P=0.001 respectively). Conclusion: Infants' gestational age and birth weight were associated with hospital readmission within thirty days after discharge, so that the infants with lower gestational age and birth weight were more likely to be hospitalized again after discharge.